Exonic deletions of AUTS2 in Chinese patients with developmental delay and intellectual disability. Issue 2 (6th November 2015) - Fan, Yanjie; Qiu, Wenjuan; Wang, Lili; Gu, Xuefan; Yu, Yongguo
Abstract : Genomic rearrangements involving dosage change of genes have been implicated in a range of developmental disorders. Increasing evidences suggest copy number variations (CNVs) of autism susceptibility candidate gene 2 ( AUTS2 ) are associated with a syndromic form of developmental delay and intellectual disability. However, the genetic and clinical profiles involving AUTS2 variations have not been fully characterized in Asian patients yet, and the outcome of treatments has not been reported. Here we report de novo exonic deletions of AUTS2 detected by chromosomal microarray analysis (CMA) in three Chinese children referred to the clinic for developmental delay, including two deletions involving only exon 6 (98.4 and 262 kb, respectively) and one deletion involving the C‐terminal of AUTS2 (2147 kb). The phenotypic presentations of these three patients were described and compared with previous cases in literature. In addition, we presented the outcome of hormonal treatment for short stature in one patient. © 2015 Wiley Periodicals, Inc.